Archaeopteryx - Oliver, Rupert (Vero Beach, FL : Rourke Enterprises, 1984)
Describes the physical characteristics, habits and natural environment of the winged dinosaur known as Archaeopteryx.
Keywords: Archaeopteryx -- Juvenile literature; Dinosaurs -- Juvenile literature